ОСОБЛИВОСТІ МІЖБЮДЖЕТНИХ ВІДНОСИН В КОНТЕКСТІ ДОСЯГНЕННЯ ФІНАНСОВОЇ СПРОМОЖНОСТІ ТЕРИТОРІАЛЬНИХ ГРОМАД - Возняк, Галина Василівна (Науковий журнал «Світ фінансів», 2017)
Возняк Г. В. Особливості міжбюджетних відносин в контексті досягнення фінансової спроможності територіальних громад. Висвітлено особливості системи міжбюджетних відносин в умовах реформування місцевого самоврядування в Україні. Проведено аналіз бюджетно-податкових новацій, які дали змогу розширити принципи самостійності місцевих бюджетів, перерозподілити видаткові повноваження між органами влади різних рівнів і сформувати передумови для активізації процесу добровільного об’єднання територіальних громад. Обґрунтовано ризики поглиблення бюджетної децентралізації, а саме: надмірна трансфертна залежність територіальних громад від державного бюджету; низький рівень кадрового потенціалу громади; низька фінансова самостійність місцевого самоврядування тощо. Запропоновано напрями зміцнення фінансової спроможності територіальних громад. Возняк Г. В. Особенности межбюджетных отношений в контексте достижения финансовой состоятельности территориальных общин. Освещены особенности системы межбюджетных отношений в условиях реформирования местного самоуправления в Украине. Проведен анализ бюджетно-налоговых новаций, позволяющих расширить принципы самостоятельности местных бюджетов, перераспределить расходные полномочия между органами власти различных уровней и сформировать предпосылки для активизации процесса добровольного объединения территориальных общин. Обосновано риски углубления бюджетной децентрализации, а именно: чрезмерная трансфертная зависимость территориальных общин от государственного бюджета; низкий уровень кадрового потенциала общества; низкая финансовая самостоятельность местного самоуправления. Предложены направления укрепления финансовой состоятельности территориальных общин. Vozniak H. Features of intergovernmental relations in the context of achieving financial viability of local communities. Introduction. In the conditions of the implementation of the government’s decentralization reform, local communities received the real opportunities for increasing the resources which can be used for development. One of the conditions, which provides their economic development, is to create an effective system of intergovernmental relations, aimed to optimizing fiscal decentralization and clear definition of the powers of local government. The increasing interest to the problem of expanding of local communities financial capacity caused by the necessity to find improved mechanisms for incomes separation between the elements of the budget system and types of budgets. Purpose. The purpose of this article is to study of intergovernmental relations in the context of achieving financial viability of local communities and to summarize the preliminary results of the reform. Results. The features of intergovernmental relations in local government reform in Ukraine are highlighted. The fiscal innovations, which extends the autonomy principles of local budgets, reallocates expenditure responsibilities between levels of government and creates conditions for intensification of the process of voluntary association of municipalities, have been analyzed. The first phase of fiscal decentralization in Ukraine has been estimated. It has been shown that despite the strengthening of the solvency of local budgets, the negative trends is intensified: excessive centralization of budgetary decisions; imperfect distribution of functional responsibilities and rights between the central and local governments; low human resource capacity of the community; low financial autonomy of local government and so on. The risks of the further deepening the fiscal decentralization have been justified. Conclusions. It was suggested the directions for increasing financial capacity of local communities in the introduction of industry standards of public services, which should increase the efficiency of planning and using of public funds at all levels; in the improving the basic and reverse subsidies calculations and in the estimation the risks of the fiscal decentralization.